Automated quantitative pupillometry as a predictor for transtentorial brain herniation in patients with malignant acute ischemic stroke. - Catherine Park; So Young Park; Min Kim; Bumhee Park; Ji Man Hong (PLoS ONE)
Brain herniation can be a life-threatening condition, resulting in poor prognosis and higher fatality rates. We examined whether quantitative characteristics of sequential pupillary light reflex (PLR) could serve as biomarkers for identifying brain herniation in fatal acute stroke cases with anterior circulation involvement admitted to neurological intensive care unit (Neuro-ICU). Automatic pupillometer assessed PLR automatically every 4-6 hours, measuring eight specific features: NPi (Neurological pupil index) score, initial resting and constriction pupil size, constriction change, constriction velocity, constriction latency, and dilation velocity. Generalized estimating equations were used to analyze the main effects of assessment time (3-to-0 hours, just before brain herniation, and 27-to-21 hours, considerably before) and clinical groups. The study involved 59 patients (mean age 68.8 ± 1.6 years, 23 females) divided into herniation (n = 10) and non-herniation (n = 49) groups. The herniation group exhibited significantly lower ipsilateral NPi scores at 3-to-0 hours (1.80 ± 0.44, p < 0.0001) compared to 27-to-21 hours (4.26 ± 2.21). Additionally, the herniation group had a larger ipsilateral pupil size at constriction at 3-to-0 hours (4.01 ± 0.40 mm) compared to 27-to-21 hours (2.11 ± 0.17 mm). Specifically, at 3-to-0 hours, the herniation group had lower NPi scores (1.80 ± 0.44 vs. 3.97 ± 0.13, p < 0.0001) and larger pupil size at constriction (4.01 ± 0.04 mm vs. 2.90 ± 0.10 mm, p = 0.007) compared to the non-herniation group. These findings suggest that evaluating PLR characteristics can aid in the early identification of brain herniation, facilitating timely triage and appropriate surgical management.